PENGARUH TRANSPARANSI, AKUNTABILITAS, DAN PARTISIPASI MASYARAKAT PADA PENGELOLAAN ALOKASI DANA DESA (ADD) TERHADAP PEMBANGUNAN DESA - Jaa, Emilianus; Sulistyo, Sulistyo; Setiyowati, Supami Wahyu (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2019)
The purpose of this study is to find out and analyze (1) the simultaneous significant influence of transparency, accountability and community participation in managing village fund allocation to village development. (2) partially significant influence of transparency in the management of village fund allocation on village development. (3) partially significant influence of accountability in the management of village fund allocations on village development, (4) partially significant influence of community participation in managing village fund allocations on village development. This study uses a quantitative approach. This research was conducted in the village of Gurung Turi, East Manggarai Regency. Data collection techniques in this study used a questionnaire with sampling techniques using simple random sampling. The data analysis technique used is multiple linear regression analysis techniques. The results showed that overall the variables of transparency, accountability and community participation in the Village Fund Allocation Management had an influence on Village Development. The principles of transparency, accountability and community participation have been implemented. With the implementation of the three principles of transparency, accountability, and community participation it has an influence on village development by showing the level of development of the desert village that has begun to increase.